Perceived Positive and Negative Life Changes in Testicular Cancer Survivors - Sigrun Vehling; Karin Oechsle; Michael Hartmann; Carsten Bokemeyer; Anja Mehnert-Theuerkauf (Medicina, 2021)
Background and objectives: Despite a generally good prognosis, testicular cancer can be a life-altering event. We explored perceived positive and negative life changes after testicular cancer in terms of frequency, demographic and disease-related predictors, and associations with depression and anxiety. Materials and methods: All testicular cancer survivors receiving follow-up care at two specialized outpatient treatment facilities were approached at follow-up visits or via mail. We assessed a total of N = 164 patients (66% participation rate, mean time since diagnosis: 11.6 years, SD = 7.4) by the Posttraumatic Growth Inventory (PTGI, modified version assessing positive and negative changes for each of 21 items), Patient-Health-Questionnaire-9 (PHQ-9), and Generalized-Anxiety-Disorder-Scale-7 (GAD-7). We conducted controlled multivariate regression analyses. Results: Most survivors (87%) reported at least one positive change (mean number: 7.2, SD = 5.0, possible range: 0–21). The most frequent perceived positive changes were greater appreciation of life (62%), changed priorities in life (62%), and ability rely on others (51%). At least one negative change was perceived by 33% (mean number of changes: 1.1, SD = 2.5). Negative changes were most frequent for decreases in self-reliance (14%), personal strength (11%), and ability to express emotions (9%). A higher socioeconomic status was associated with more positive changes (β = 0.25, 95% CI 0.08 to 0.42); no other association with demographic and disease-related predictors emerged. While positive life changes were not associated with depression (β = −0.05, 95% CI −0.17 to 0.07) and anxiety (β = 0.00, 95% CI −0.13 to 0.13), more negative life changes were significantly associated with higher depression (β = 0.15, 95% CI −0.03 to 0.27) and anxiety (β = 0.23, 95% CI 0.11 to 0.36). There was no significant interaction of positive and negative changes on depression or anxiety. Conclusions: Although positive life changes after testicular cancer are common, a significant number of survivors perceive negative changes in life domains that have been primarily investigated in terms of personal growth. Early identification of and psychosocial support for patients who perceive predominantly negative changes may contribute to prevention of prolonged symptoms of anxiety and depression.